2006
DOI: 10.1101/gad.385606
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines regulate postnatal hematopoietic stem cell expansion: opposing roles of thrombopoietin and LNK

Abstract: The role of cytokines as regulators of hematopoietic stem cell (HSC) expansion remains elusive. Herein, we identify thrombopoietin (THPO) and the cytokine signaling inhibitor LNK, as opposing physiological regulators of HSC expansion. Lnk −/− HSCs continue to expand postnatally, up to 24-fold above normal by 6 mo of age. Within the stem cell compartment, this expansion is highly selective for self-renewing long-term HSCs (LTHSCs), which show enhanced THPO responsiveness. As self-renewing hematopoietic stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
115
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 36 publications
9
115
0
1
Order By: Relevance
“…As stated before, Lnk is highly expressed in HSC, so as expected, Lnk -/--derived HSC show an increased capacity to proliferate and to self-renew together with an increase in the quiescent fraction. These effects on HSC homeostasis are due to abnormal TPO signalling in these cells, that results from an enhanced TPO hypersensibility, increased TPO-dependent activation of Akt, STAT5 and down-regulation of p38MAPK (Ema et al, 2005;Buza-Vidas et al, 2006;Seita et al, 2007;Bersenev et al, 2008). These findings therefore confirm that Lnk controls TPO-induced self-renewal, quiescence and proliferation of HSC.…”
Section: Signalling Pathways In Haematopoietic Cellssupporting
confidence: 75%
See 1 more Smart Citation
“…As stated before, Lnk is highly expressed in HSC, so as expected, Lnk -/--derived HSC show an increased capacity to proliferate and to self-renew together with an increase in the quiescent fraction. These effects on HSC homeostasis are due to abnormal TPO signalling in these cells, that results from an enhanced TPO hypersensibility, increased TPO-dependent activation of Akt, STAT5 and down-regulation of p38MAPK (Ema et al, 2005;Buza-Vidas et al, 2006;Seita et al, 2007;Bersenev et al, 2008). These findings therefore confirm that Lnk controls TPO-induced self-renewal, quiescence and proliferation of HSC.…”
Section: Signalling Pathways In Haematopoietic Cellssupporting
confidence: 75%
“…In contrast to SH2-B and APS, Lnk is mainly expressed in haematopoietic cells, notably in haematopoietic stem cells (HSC), and haematopoietic (lymphoid and myeloid) progenitors. Moreover, Lnk expression is upregulated by certain cytokines important for the development and function of these haematopoietic cells, such as SCF, thrombopoietin [TPO], and erythropoietin [EPO] (Kent et al, 2008;Buza-Vidas et al, 2006;Gerry et al, 2009aGerry et al, , 2009bBaran-Marszak et al, 2010). Interestingly, Lnk is also highly expressed in endothelial cells and its expression is also induced by Tumor Necrosis Factor (TNF)- (Fitau et al, 2006;Kwon et al, 2009).…”
Section: Structure Origin and Cell Expressionmentioning
confidence: 99%
“…Loss of function studies have implicated cellintrinsic factors such as p21 (Cheng et al, 2000), GFI1 (Hock et al, 2004), and LNK (Buza-Vidas et al, 2006) as physiological negative regulators of hematopoietic stem cell (HSC) maintenance. Several extrinsic factors, including TGF- (Larsson and Karlsson, 2005), IFN- (Yang et al, 2005), and IL-3 (Yonemura et al, 1996), as well TNF Dybedal et al, 2001), have been demonstrated to negatively affect HSC growth and maintenance in vitro.…”
Section: Br Ief Definitive Repor Tmentioning
confidence: 99%
“…TPO is produced primarily in the liver (9) and Mpl is expressed on platelets, megakaryocytes and their progenitors, and within the HSC compartment, including on cells with long-term hematopoietic reconstituting capacity (6,10,11). Several lines of evidence support a model in which TPO production is constant and that the concentration of available circulating TPO is controlled by the mass of Mpl receptors available to internalize the cytokine.…”
mentioning
confidence: 99%